Hubungan Analisis Kredit Terhadap Kualitas Pembiayaan KPR pada PT XYZ Cabang Batam - Agus Supriyadi; Dwi Kartikasari (Politeknik Negeri Batam, 2015)
This study aims to determine the relationship of credit analysis toward the quality of mortgage financing in PT XYZ Branch Office Batam. This study used a descriptive approach and using secondary data obtained from the consumer unit. The research sample totaled 275 data. The collected data are then analyzed statistically by analysis of correlation Kendall tau and Spearman rho using SPSS version 20.00. The results showed that (1) There is no relationship between capacity aspects of the quality of financing (2) There is a relationship between collateral aspects of the quality of financing (3) There was no relationship between aspects of the character of the quality of financing. The aspect ratio of principal loan collateral or the value of the collateral is a variable that has more ties to the positive direction of the quality of financing in this study.